Diagnostic tools in coronavirus disease 2019 associated mucormycosis – do we need three-dimensional computed tomography?. Issue 12 (17th December 2022) - Gupta, G; Shakrawal, N; Banthia, S; Nehara, H R; Chand, D
Abstract: Objective: Three-dimensional computed tomography reconstruction of the face has recently been presented as a newer diagnostic tool in coronavirus disease 2019 associated mucormycosis. This study was conducted to compare three-dimensional computed tomography reconstruction with conventional two-dimensional computed tomography in coronavirus disease 2019 associated mucormycosis. Methods: A total of 123 mucormycosis patients underwent three-dimensional computed tomography reconstruction after a comprehensive clinical investigation. The involvement of the facial skeleton was noted. Results: The anterior maxillary wall was most commonly involved (9.8 per cent). Involvement of the lateral maxillary wall was noted in 6.5 per cent of patients. Sixty-seven patients (54.5 per cent) underwent endoscopic surgery, 22 (17.9 per cent) underwent open surgical procedures, and 12 (9.8 per cent) had combined endoscopic and open surgical procedures. In 21 patients (17.1 per cent), open surgery was performed in the first instance based on additional three-dimensional computed tomography findings, and revision surgical procedures were avoided. Conclusion: Three-dimensional computed tomography of the face was found to be superior in determining the extent of disease. It reduces delays in diagnosis, facilitates surgical planning and minimises the need for multiple surgical procedures.